Toxicologie industrielle et vieillissement - Ginette Truchon; Guy Perrault; Robert Tardif (Perspectives Interdisciplinaires sur le Travail et la Santé)
Several physiological and biochemical changes accompany aging and can affect the metabolism of chemicals and the body’s response. A literature review was carried out to identify these changes and their potential impact on the health of aging workers. The main effects listed are a reduction in renal and hepatic function and a reduction in cardiac output with age. The final consequence most often observed is an increase in the time required to eliminate the substances from the body. Some studies also suggest a more significant response or effect in the elderly, compared to younger individuals, for the same blood concentration of the toxic substance.